The Planet's Stressed River Basins: Too Much Pressure or Too Little Adaptive Capacity?. Issue 10 (8th October 2019) - Varis, Olli; Taka, Maija; Kummu, Matti
Abstract: Freshwater is one of the most critical elements for sustainable development of ecosystems and societies. River basins, concomitant with administrative zones, form a common unit for freshwater management. So far, no comprehensive, global analysis exists that would link the ecological challenges of the planet's river basins to the capacity of the societies to cope with them. We address this gap by performing a geospatial resilience analysis for a global set of 541 river basins. We use the social‐ecological systems approach by relating three ecological vulnerability factors (human footprint, natural hazards, and water scarcity) with three adaptive capacity factors (governance, economy, and human development), based on temporal trajectories from 1990 to 2015. Additionally, we examine resilience by subtracting ecological vulnerability from adaptive capacity. The most striking result is the fundamentally different patterns of controlling factors of the resilience in different developing regions, particularly those of Africa and Asia. Their root causes are particularly low adaptive capacity in Africa and high ecological vulnerability in Asia. Alarmingly, the difference between those continents grew within the study period. Finally, this study highlights the rapid dynamics of adaptive capacity in comparison to ecological vulnerability, the latter having more inertia. Their fragile balance is of our interest; they can either support or counteract each other depending on the geographic location. Plain language summary: The ongoing global environmental change highlights the critical role of freshwater for sustainable development of ecosystems and human societies. Resilience is the capacity to absorb disturbance and reorganize while undergoing changes. In this study, we perform a spatial analysis for 541 watersheds to identify the drivers of this resilience. We define resilience of each basin by first examining their adaptive capacity, which is a combination of governance, economy, and human development. We then define ecological vulnerability by combining human footprint, natural hazards, and water scarcity into one index. To conclude, resilience indicates the strength of community's adaptive capacity in the presence of ecological vulnerability. Our results indicate the different patterns resilience across the globe, pointing out how the similarly low resilience in Africa and Asia is caused by low adaptive capacity and high ecological vulnerability, respectively. Our temporal analysis 1990–2015 shows how this difference has been increasing over time. Interestingly, adaptive capacity was more dynamic over time, compared to more constant ecological vulnerability. The examined balance between adaptability and vulnerability provides a useful tool for managing the resilience of freshwater resources. Key Points: We quantify resilience of the world's river basins using geospatial social‐ecological systems approach The approach uses composite indicators of both adaptive capacity and ecological vulnerability Africa and Asia show the lowest resilience, which is due to low adaptive capacity in Africa and high ecological vulnerability in Asia